Synthesis, characterization, and photodynamic therapy activity of 5, 10, 15, 20-Tetrakis(carboxyl)porphyrin. Issue 12 (15th June 2019) - Zhang, Zhao; Yu, Hua-Jun; Wu, Shang; Huang, Hui; Si, Li-Ping; Liu, Hai-Yang; Shi, Lei; Zhang, Hai-Tao
Graphical abstract: Abstract: Water-soluble porphyrins are considered promising drug candidates for photodynamic therapy (PDT). This study investigated the PDT activity of a new water-soluble, anionic porphyrin (1-Zn ), which possesses four negative charges. The photodynamic anticancer activity of1-Zn was investigated by the MTT assay, with mTHPC as a positive control. The cellular distribution was determined by fluorescence microscopy. Holographic and phase contrast images were recorded after1-Zn treatment with a HoloMonitor™ M3 instrument. The inhibition of A549 cell growth achieved by inducing apoptosis was investigated by flow cytometry and fluorescence microscopy. DNA damage was investigated by the comet assay. The expression of apoptosis-related proteins was also measured by western blot assays.1-Zn had better phototoxicity against A549 cells than HeLa and HepG2 cancer cells. Interestingly, 1-Zn was clearly located almost entirely in the cell cytoplasmic region/organelles. The late apoptotic population was less than 1.0% at baseline in the untreated and only light-treated cells and increased to 40.5% after1-Zn treatment and irradiation (P < 0.05).1-Zn triggered significant ROS generation after irradiation, causing ΔΨm disruption (P < 0.01) and DNA damage.1-Zn induced A549 cell apoptosis via the mitochondrial apoptosis pathway. In addition, 1-Zn bound in the groove of DNA via an outside binding mode by pi-pi stacking and hydrogen bonding.1-Zn exhibits good photonuclease activity and might serve as a potential photosensitizer (PS) for lung cancer cells.